The Relationship Between Anxiety and Quality of Life Among Older Adults During the COVID-19 Pandemic - Nova Aprialis Tyaningsih; Nur Melliza (Pubfine Media Group, 2025)
Introduction: The Covid-19 pandemic has affected not only physical health but also the psychological well-being and quality of life of older adults. Anxiety related to health risks, social isolation, and economic uncertainty has become increasingly prevalent among the elderly population. This study aimed to determine the relationship between anxiety levels and quality of life among older adults during the Covid-19 pandemic in Dusun Karang Menjangan, Bulurejo Village, Tempursari District. Methods: A quantitative analytic observational design was used, involving 62 elderly respondents selected through purposive sampling. Data were collected using standardized questionnaires to measure anxiety levels and quality of life. Statistical analysis was performed using the Spearman’s rho correlation test to assess the relationship between anxiety and quality of life variables. Results: Findings indicated that most respondents experienced moderate anxiety (92%) and reported a moderate quality of life (87%) during the pandemic. The correlation test showed no significant relationship between anxiety and quality of life (p = 0.251; r = -0.148). The negative correlation value indicated an inverse but weak relationship, suggesting that higher anxiety levels tended to be associated with lower quality of life, although not statistically significant. Conclusion: There was no significant relationship between anxiety and quality of life among older adults during the Covid-19 pandemic. Despite this, the high prevalence of moderate anxiety highlights the importance of continuous psychosocial support, family involvement, and community-based interventions to maintain the mental and emotional well-being of the elderly.